Особливості іконографічної традиції зображень Св. Миколи Мірлікійського у дрібній пластиці Київської Русі - Бурковська, Л. (Народна творчість та етнографія, 2008)
An author analyzed works which represent image of saint Nickolas Mirlikiyskyi in the fine plastic art of Kyiv Russ. The author examined of features of adaptation of Byzantine models in the Old Russian art.